Membrane Heterogeneity Beyond the Plasma Membrane - Wang, Hong-Yin; Bharti, Deepti; Levental, Ilya (Frontiers in Cell and Developmental Biology, 2020)
The structure and organization of cellular membranes has received intense interest, particularly in investigations of the raft hypothesis. The vast majority of these investigations have focused on the plasma membrane of mammalian cells (PM), yielding significant progress in understanding membrane heterogeneity in terms of lipid composition, molecular structure, dynamic regulation, and functional relevance. In contrast, investigations on lipid organization in other membrane systems have been comparatively scarce, despite the likely relevance of membrane domains in these contexts. In this review, we summarize recent observations on lipid organization in organellular membranes including ER, Golgi, endo-lysosomes, lipid droplets, as well as secreted membrane systems like lung surfactant, milk fat globule membranes and viral membranes. Across these non-PM systems, it appears that the biophysical principles underlying lipid self-organization contribute to lateral domains, provide novel insights into the fascinating nature of lipid compartmentalization of biological membranes.